Determination of heavy metal (Cu, Cd, and Pb) concentrations in surface waters and sediments of rivers in Batan Bay, Aklan. - Erbina, Mitzi Vita Catalayban
Batan Bay serves as a major source of aquatic organisms in Aklan and as well as Western Visayas. However in recent years, a decline in fishery production in the bay has been reported. This study analyzed the levels of copper (Cu), and lean (Pb)in sediments and water samples collected in 18 sites from river tributaries of Batan Bay, in order to determine the importance of heavy metal pollution in the area. Samples were analyzeed using Varian 55B Flame Atomic Absorption Spectrometer (FAAS). Results showed that Cu concentrations in sediments ranged from 22.53-69.11 mg/kg-dry weight. On the other hand, Pb and Cd levels were significantly lower than Cu and range from 7.74-24.28 mg/kg-dry weight and 0.78 - 2.79 mg/kg-dry weight, respectively. It was observed that site 17 (Lupon Bridge) had the highest Cu concentration in sediments among 18 sites. While site 9 had the highest concentration in Cd and Pb. In water samples, highest concentration of heavy metal was observed for Pb (below detection limit - 0.32 mg/L). Cadmium and Cu concentrations ranged from below detection - 0.08 mg/L and below detection limit - 0.06 mg/L, respectively. As observed, site 1 (Batan Port) had the highest concentrations of Cu, Cd and Pb in surface among 18 sites. overall, the heavy metal concentration in sediments and surface water in the areas that are near the ports are high that may due to shipping activities these areas. High concentration of heavy metals may pose risks to aquatic organisms and may results to a decrease in the fish production in Batan Bay, as well as contamination of fishery products from contaminated sites. Results from the study provide information on the levels of heavy metals in the area that might reflect on the quality of the aquatic environment.